La Plage urbaine spontanée, une nouvelle forme d’appropriation oisive de l’espace public - Maroua En-nejjari; Ignacio Requena; Daniel Siret (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Spontaneous urban beaches are contemporary public spaces where city dwellers behave as if they were on the beach, although these places have not been apparently planned for this purpose. Such urban public spaces, often located along the waterside, reflect the emergence of a new approach to body and idleness in the public realm on the one hand, and the trend of functional diversion and spontaneous appropriation of the city on the other hand. This paper sheds light on the identification of the spatio-temporal, socio-cultural and political conditions of the emergence of a spontaneous beach situation in the urban environment. To do so, we have conducted an in-situ field survey in the city of Nantes in the summer of 2018, followed by a survey work out of beach situations, conducted with city dwellers and public officials of the city in 2019.